Evaluation of the Georgia Elementary School Climate Survey for elementary school children - Victor Martinelli; Milosh Raykov (International Journal of Emotional Education, 2021)
School climate is a vital aspect of school life that influences students’ emotional well- being, social relations and academic achievement. Therefore, educators need to monitor school climate to nurture good interpersonal relations and students’ positive experiences in school. To achieve this objective, educators and psychosocial support services in schools need valid and reliable instruments to measure and monitor school climate. A review of the instruments for measuring school climate shows that they are available in several countries, but their application in these diverse settings requires evaluation and adaptation to the different conditions where they are being implemented. This study is part of a larger international project that examines the use of the Georgia Elementary School Climate Survey across many countries. The project includes students’, parents’, and educators’ perceptions of school climate and aims to address the existing shortage of valid instruments of this important indicator of school life in Maltese educational settings. This study was based on responses from 592 children from five primary schools and focused on evaluating an adapted version of the Georgia Elementary School Climate Survey for primary school children. The study indicates that the slightly adapted scale has a good structure and acceptable internal consistency, indicating that the scale can be used in school practice. Based on the analysis of the items in the questionnaire, the study provides some suggestions for further development of this scale to respond better to the local educational setting.